PENGGUNAAN AIR KELAPA UNTUK MENINGKATKAN PERKECAMBAHAN DAN PERTUMBUHAN PALEM PUTRI (VEITCHIA MERILUI) - Sujarwati '; Siti Fathonah; Elna Johani; Herlina ' (Jurnal Sagu, 2011)
The present study was aimed to Ttnd out the most effective concentration of coconut water on the seedgermination and seedling growth of Veitchia merillii. The study used two experiments: seed germination andseedling growth. The study used Completely Randomized Design with live coconut water concentrations: 0%(K„). 25% (K,), 50% (K,"), 75% (K,), and 100% ( K > Data were subjected to analysis ot variance andDuncan's Multiple Range test at 95% significance level. The result showed thai seed soaking in coconutwater improved the germination percentage. The most cllective treatment in increasing the seed germinationis seed soaking in 75% coconut water concentration. Sprinkled the seedling with coconut water couldincrease plant height, length of leaf, and length of root, hut had not increase the number of leaf. There w as noliigniticant effect in coconut water concentration.